A Qualitative Study to Understand the Barriers and Enablers in Implementing an Enhanced Recovery After Surgery Program. Issue 1 (January 2015) - Pearsall, Emily A.; Meghji, Zahida; Pitzul, Kristen B.; Aarts, Mary-Anne; McKenzie, Marg; McLeod, Robin S.; Okrainec, Allan
<x xml:space="preserve">Abstract</x> Objective: Explore the barriers and enablers to adoption of an Enhanced Recovery after Surgery (ERAS) program by the multidisciplinary perioperative team responsible for the care of elective colorectal surgical patients. Background: ERAS programs include perioperative interventions that when used together have led to decreased length of stay while increasing patient recovery and satisfaction. Despite the known benefits of ERAS programs, uptake remains slow. Methods: Semistructured interviews were conducted with general surgeons, anesthesiologists, and ward nurses at 7 University of Toronto-affiliated hospitals to identify potential barriers and enablers to adoption of 18 ERAS interventions. Grounded theory was used to thematically analyze the transcribed interviews. Results: Nineteen general surgeons, 18 anesthesiologists, and 18 nurses participated. The mean time of each interview was 18 minutes. Lack of manpower, poor communication and collaboration, resistance to change, and patient factors were cited by most as barriers. Discipline-specific issues were identified although most related to resistance to change. Overall, interviewees were supportive of implementation of a standardized ERAS program and agreed that a standardized guideline based on best evidence; standardized order sets; and education of the staff, patients, and families are essential. Conclusions: Multidisciplinary perioperative staff supported the implementation of an ERAS program at the University of Toronto–affiliated hospitals. However, major barriers were identified, including the need for patient education, increased communication and collaboration, and better evidence for ERAS interventions. Identifying these barriers and enablers is the first step toward successfully implementing an ERAS program.